Menumbuhkan Jiwa Berwirausaha - Slamet, Slamet (UIN Maulana Malik Ibrahim Malang, 2005)
Entrepreneurs are people with the ability seeing and assessing the available chances, collecting the necessary resources to take the advantages from it, and doing the appropriate act to ensure the success. Entrepreneurs are act-oriented people and have high motivation to take a risk in achieving their goals. Besides the definition of entrepreneurship, this article presents the must-have personalities of an entrepreneur, such as confidence, enthusiasm, honesty, and introspective; some aspects to develop the work ethic in entrepreneurship is also presented here. It is noteworthy for the youths that work enthusiasm is not only about earning money but more about self-actualization and carrying out the mandate. Moreover, work is a way to show our gratefulness toward our Creator, Allah swt. Para wirausaha adalah orang-orang yang mempunyai kemampuan melihat dan menilai kesempatan-kesempatan yang ada, mengumpulkan sumber daya yang dibutuhka guna mengambil keuntungan daripadanya dan mengambil tindakan yang tepat guna memastikan kesuksesan. Para wirausaha adalah individu-individu yang berorientasi pada tindakan dan bermotivasi tinggi yang mengambil resiko dalam mengejar tujuannya. Selain pengertian kewirausahaan, artikel ini membahas kepribadian wirausaha seperti percaya diri, semangat, jujur, dan mawas diri; juga beberapa hal untuk membangun etos kerja di bidang kewirausahaan. Penting untuk disadari kaum muda saat ini bahwa semangat bekerja tidak hanya sekedar mencari uang tetapi lebih kepada untuk aktualisasi diri dan melaksanakan amanah. Lebih lagi, bekerja ialah bentuk rasa syukur seorang manusia terhadap Sang Pencipta.